Utilizing river bank stabilization and reactive stream stabilization as best management practices for achieving total maximum daily load regulations - Son, JiHee, author; Carlson, Kenneth H., advisor; Sharvelle, Sybil, committee member; Borch, Thomas, committee member (Colorado State University. Libraries, 2010)
Phosphorus is recognized as a limiting factor for growth of aquatic organisms in surface water bodies. When excess amounts of this nutrient are discharged into a stream, biomass of phytoplankton starts to increase and eutrophication can result. A Reactive Stream Stabilization (RS2) structure has been developed to stabilize the stream bank and minimize release of some agricultural nonpoint source pollutants through erosion from farms, waste sites, and animal feed lots to the stream. The RS2 system was studied for its nutrient (nitrogen and phosphorus) removal efficiency from 2003 to 2006 at the Colorado State University. Based on this study at CSU, a RS2 structure was designed and installed along the bank of the Little Bogue Creek near Grenada, Mississippi in November 2008. The scope of the research for this Master's thesis research was to assist in design and installation of a field scale RS2 structure and to conduct assessment of the initial nutrient removal performance of the system. The reactive barrier of the installed RS2 has shown high concentrations of Al and organic matter, design criteria intended to promote adsorption of phosphorus (P) and facilitate nitrogen (N) removal through denitrification. The performance of the RS2 structure was examined from the soils, monitoring wells and the stream waters that were sampled in May and July, 2009. The mean concentration of aluminum from the reactive barrier was 2.1 mg/g soil and organic matter from the monitoring wells in the bank was 4.68 mg/L which were significantly greater than the surrounding area (p<0.05). Soil Mehlich-3 P and total P (TP) were decreased by 55 % and 30 %, and 40 % of TN and 51 % of nitrate in the ground water were removed through the RS2. The RS2 is expected retain P efficiently although accumulation of P has not yet been observed. From this research, the design objectives of the RS2 structure have been satisfied and the initial sampling data shows promise. Future research will be conducted to verify the effectiveness of RS2 structures for achieving TMDL regulations.
Keywords: Watershed management; Watershed management -- Bear Creek Watershed (Ala. and Miss.); Runoff -- Management